Efficient resource allocation for China's 3G - Yu Cheng
The all-IP DiffServ model is expected to be the most promising architecture for QoS provisioning in China's next-generation wireless networks, due to its scalability, convenience for mobility support, and capability of interworking heterogeneous radio access networks. This article focuses on efficient resource allocation in a wireless DiffServ architecture. Resource utilization efficiency is particularly important for China's wireless networks as the mobile user density in China is and will continue to be much higher than that in other countries. More specifically, we propose a novel buffer sharing scheme to provide assured service for real-time layer-coded multimedia traffic, which can guarantee the specific packet loss requirement of each layer with UDP as the transport layer protocol. An adaptive optimal buffer configuration can be applied to achieve maximum resource utilization over the time-varying channel. Assured service is also provided to TCP data traffic for guaranteed throughput, where the cross-layer coupling between the TCP layer and link layer is exploited to efficiently utilize the wireless resources.
Keywords: 3G wireless network; 4G wireless network; QoS; TCP data traffic; Adaptive optimal buffer configuration; All-IP DiffServ model; Buffer sharing scheme; Heterogeneous radio access network; Mobility support; Packet loss; Quality of service; Real-time layer-coded multimedia traffic; Resource allocation; Time-varying channel; Transport control protocol; Transport layer protocol